COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN EKOWISATA PEKALONGAN MANGROVE PARK - Tsalitsa Farah Jazila; Dewi Erowati (Journal of Politic and Government Studies, 2026)
Pekalongan Mangrove Park (PMP) is an ecotourism destination that functions as a tourist attraction, a mangrove conservation area, and an environmental education platform for coastal erosion mitigation. However, its management still faces various obstacles, such as limited facilities, the need for environmental restoration, and suboptimal educational and conservation functions. This study aims to analyze the implementation of collaborative governance in PMP ecotourism management. This study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results indicate that the collaborative process has not been optimal. Dialogue between formal actors has been conducted, but it is not structured and does not involve the community. The trust and commitment that has been formed tend to be dominated by formal actors. There is a shared understanding of the goals of mangrove conservation, but the community has not been substantively involved. Interim results achieved are limited to the sustainability of tourism operations, not to community empowerment. Overall, collaborative governance in the management of Pekalongan Mangrove Park ecotourism does not meet the principles of participatory, inclusive, and equal because the community as a local stakeholder has not been actively involved.